2023
DOI: 10.1080/0886022x.2023.2209200
|View full text |Cite
|
Sign up to set email alerts
|

The association between dietary inflammation index and bone mineral density: results from the United States National Health and nutrition examination surveys

Abstract: Objective To investigate the associations of dietary inflammation index (DII) with bone density and osteoporosis in different femoral areas. Methods The study population was selected from the National Health and Nutrition Examination Survey (NHANES) with the exclusion criteria of age 18, pregnancy, or missing information on DII, femoral bone marrow density (BMD), estimated glomerular filtration rate (eGFR), and urine albumin-to-creatinine ratio (UACR), or had diseases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…The CDAI serves as a tool to quantify the potential antioxidant capacity of one’s daily diet ( 21 ). Existing literature suggests that CDAI is negatively correlated with osteoporosis ( 22 ), hypertension ( 23 ), depression ( 20 ), and cardiovascular disease mortality ( 24 ). Furthermore, it is also associated with specific inflammatory biomarkers such as IL-1β and TNFα ( 25 ), which are known to be elevated in constipated populations ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The CDAI serves as a tool to quantify the potential antioxidant capacity of one’s daily diet ( 21 ). Existing literature suggests that CDAI is negatively correlated with osteoporosis ( 22 ), hypertension ( 23 ), depression ( 20 ), and cardiovascular disease mortality ( 24 ). Furthermore, it is also associated with specific inflammatory biomarkers such as IL-1β and TNFα ( 25 ), which are known to be elevated in constipated populations ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Canadian Multicenter Osteoporosis Study showed that an increased intake of protein and nutrient-dense foods, such as fruits, vegetables, and whole grains, was associated with a lower fracture risk [68]. Similar trends were seen in different diets among different cultures.…”
Section: Non-pharmacological Treatment Optionsmentioning
confidence: 81%
“…CKD patients with HPI do not benefit from developing higher femoral BMD, and those with LDI do not develop lower femoral BMD. However, in a previously published study [ 55 ], it was found that a high dietary inflammation index is independently associated with decreased bone mineral density (BMD) in the femoral regions. In the present study, we found similar results regarding lumbar BMD in the NHANES cohort.…”
Section: Discussionmentioning
confidence: 99%